O-Polysaccharide Plays a Major Role on the Virulence and Immunostimulatory Potential of Aggregatibacter actinomycetemcomitans During Periodontal Infection - Monasterio, Gustavo; Castillo, Francisca; Astorga, Jessica; Hoare, Anilei; Terraza-Aguirre, Claudia; Cafferata, Emilio A.; Villablanca, Eduardo J.; Vernal, Rolando (Frontiers in Immunology, 2020)
Aggregatibacter actinomycetemcomitans is a Gram-negative oral bacterium with high immunostimulatory and pathogenic potential involved in the onset and progression of periodontitis, a chronic disease characterized by aberrant immune responses followed by tooth-supporting bone resorption, which eventually leads to tooth loss. While several studies have provided evidence related to the virulence factors of A. actinomycetemcomitans involved in the host cell death and immune evasion, such as its most studied primate-specific virulence factor, leukotoxin, the role of specific lipopolysaccharide (LPS) domains remain poorly understood. Here, we analyzed the role of the immunodominant domain of the LPS of A. actinomycetemcomitans termed O-polysaccharide (O-PS), which differentiates the distinct bacterial serotypes based on its antigenicity. To determine the role of the O-PS in the immunogenicity and virulence of A. actinomycetemcomitans during periodontitis, we analyzed the in vivo and in vitro effect of an O-PS-defective transposon mutant serotype b strain, characterized by the deletion of the rmlC gene encoding the α-L-rhamnose sugar biosynthetic enzyme. Induction of experimental periodontitis using the O-PS-defective rmlC mutant strain resulted in lower tooth-supporting bone resorption, infiltration of Th1, Th17, and Th22 lymphocytes, and expression of Ahr, Il1b, Il17, Il23, Tlr4, and RANKL (Tnfsf11) in the periodontal lesions as compared with the wild-type A. actinomycetemcomitans strain. In addition, the O-PS-defective rmlC mutant strain led to impaired activation of antigen-presenting cells, with less expression of the co-stimulatory molecules CD40 and CD80 in B lymphocytes and dendritic cells, and downregulated expression of Tnfa and Il1b in splenocytes. In conclusion, these data demonstrate that the O-PS from the serotype b of A. actinomycetemcomitans plays a key role in the capacity of the bacterium to prime oral innate and adaptive immune responses, by triggering the Th1 and Th17-driven tooth-supporting bone resorption during periodontitis.